ANALISIS PARTISIPASI TENAGA KERJA DISABILITAS DI INDONESIA - Syahzana, Alya; Yeniwati (Universitas Negeri Padang, 2025)
This study analyzes the labor force participation of people with disabilities in Indonesia, focusing on (1) the extent to which gender influences disabled labor participation in Indonesia, (2) the extent to which education influences disabled labor participation in Indonesia, (3) the extent to which the area of residence influences disabled labor participation in Indonesia, (4) the extent to which the employment sector influences disabled labor participation in Indonesia.. Utilizing secondary data from (Susenas) 2020, this study involves 60,448 working-age individuals with disabilities. The results with logistic regression analysis indicate all of independent variables have a significant impact on the labor force participation of people with disabilities. Gender and education have a positive influence, while residence area has a negative effect. The job sector also demonstrates a positive impact, with many individuals with disabilities engaged in the agricultural sector. These findings emphasize the importance of creating an inclusive environment to enhance the participation of people with disabilities in the workforce.